2015
DOI: 10.2147/copd.s82064
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, severity, and treatment of chronic obstructive pulmonary disease in the United Kingdom by GOLD 2013

Abstract: ObjectivesIn 2013, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) updated the management strategy on COPD based on severity using a combined assessment of symptoms, degree of airflow limitation, and number of exacerbations. This study quantified prevalence and incidence of COPD in the United Kingdom and estimated disease severity by GOLD 2013 categories A/B (low risk) and C/D (high risk).MethodsThe Clinical Practice Research Datalink was used to identify COPD patients ≥40 years. Patient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 25 publications
7
34
0
4
Order By: Relevance
“…The overall finding of this study-that the prescribing of long-acting bronchodilators and ICSs in patients with COPD does not appear to align with GOLD guidelines 2-15 -is consistent with recent studies based on subgroups of patients in a variety of settings. Our observation that the most commonly dispensed first regimen involving a long-acting bronchodilator was a LABA in combination with an ICS is consistent with findings from Spain, 14 the Netherlands 33 and some, 8,11,13,34,35 but not all, 15 studies based in the UK. In several studies, researchers have had access to detailed clinical information which enabled them to assess the appropriateness of ICS use and subsequently conclude that ICS therapy was being overused.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall finding of this study-that the prescribing of long-acting bronchodilators and ICSs in patients with COPD does not appear to align with GOLD guidelines 2-15 -is consistent with recent studies based on subgroups of patients in a variety of settings. Our observation that the most commonly dispensed first regimen involving a long-acting bronchodilator was a LABA in combination with an ICS is consistent with findings from Spain, 14 the Netherlands 33 and some, 8,11,13,34,35 but not all, 15 studies based in the UK. In several studies, researchers have had access to detailed clinical information which enabled them to assess the appropriateness of ICS use and subsequently conclude that ICS therapy was being overused.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies in diverse settings have found that prescribing practice does not conform to international or national COPD treatment guidelines, or drug licencing conditions. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, these investigations have been based on subgroups of patients drawn from selected general practices, health insurance databases, or respiratory outpatient clinics or hospitals, and none have examined the longitudinal patterns of use of long-acting bronchodilator therapy in new users across an entire country.…”
Section: Summary At a Glancementioning
confidence: 99%
“…23,24 Our finding that newly identified cases tended to have mild or moderate airflow obstruction was in keeping with previous case-finding studies 10 and newly case-found patients were generally less severe than patients newly diagnosed in primary care. 25 Nevertheless, in accordance with our model, the majority of new cases could potentially benefit from inhalers, 26,27 self-management support, 28 smoking cessation 29 and vaccinations. 30 A substantial proportion (27%) also had significant breathlessness with potential to benefit from pulmonary rehabilitation.…”
supporting
confidence: 66%
“…One solution to this problem is to use primary care data, such as CPRD, linked to secondary care data, such as HES. When studying hospitalized AECOPD, for practical reasons, this is not always done,1416 and others have called for the recording hospitalizations for AECOPD in UK primary care data to be validated using HES as a reference standard 17…”
Section: Introductionmentioning
confidence: 99%